Mechanistic study of the bismuth mediated fluorination of arylboronic esters and further rational design. Issue 37 (25th August 2022) - Cai, Jiali; Zhi, Minna; Hu, Junyuan; Pu, Tingting; Guo, Kai; Zhao, Lili
Abstract : DFT calculations disclosed the catalytic mechanism of the bismuth redox catalyzed fluorination of arylboronic esters. In addition, more efficient catalysts with the framework of tethered bis-anionic ligands were rationally designed. Abstract : Density functional theory (DFT) calculations have been performed to gain insight into the catalytic mechanism of the bismuth redox catalyzed fluorination of arylboronic esters to deliver the widely used arylfluoride compounds ( Science 2020, 367, 313–317). The study reveals that the whole catalysis can be characterized via three stages: (i) transmetallation generates the Bi(iii ) intermediate 5, capitalizing on the use of KF as an activator. (ii) 5 then reacts with the electrophilic fluorination reagent 1-fluoro-2, 6-dichloropyridinium 4 via oxidative addition to give the Bi(v ) intermediate IM4A . (iii) IM4A undergoes a reductive elimination step to yield aryl fluoride compounds and regenerates the bismuth catalyst for the next catalytic cycle. Each stage is kinetically and thermodynamically feasible. The transmetallation step, with a barrier of 25.4 kcal mol −1, is predicted to be the rate-determining step (RDS) during the whole catalytic cycle. Furthermore, based on a mechanistic study, new catalysts with the framework of tethered bis-anionic ligands were designed, which will help to improve current catalytic systems and develop new bismuth mediated fluorination of arylboronic esters.